ANALISIS KINERJA BPJS KETENAGAKERJAAN KANTOR CABANG SEMARANG PEMUDA UNTUK MENINGKATKAN PERLUASAN KEPESERTAAN SEKTOR INFORMAL - Armila Ernisa Zulfa; Ida Hayu Dwimawanti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Social Insurance Program is a form of protection for increasing the welfare of all workers, including informal worker. In conducting social insurance, BPJS Ketenagakerjaan was faced by problem about expansion of membership for informal sector worker in Semarang. This research is aimed to analyse and describe the performance of BPJS Ketenagkerjaan Semarang Pemuda to increase the expansion of membership for informal sector worker based on the performance dimension also analyse and describe the factors that support and inhibit the performance. This research uses descriptive qualitative research method. The technique of collecting data in this research is using interview, observation, and documentation. The result of research shows that the performance of BPJS Ketenagakerjaan Semarang Pemuda has been good because there’re three dimensions has been done. These three dimensions are Service Quality, Responsibility, and Accountability, and one dimensions haven’t been done is Responsiveness. Factor that supporting the performance are technological factor, organizational culture, leadership, political factor, and factor that is found in research which is cooperation, while factor that inhibit the performance is social factor, and factor that is found in research is quantity of human resource. Recommendation for the result of this research is that doing optimal utilization of drive thru facility around, increasing the capacity of information system periodically, increasing cooperation with government, increasing socialization, education, and massive assistance to informal worker, and building relation with academics.